"Cool" Party, Bro: The Fraternity Use of Party Structure as a Mechanism for Control over Female Status on Campus. Issue 11 (1st November 2016) - Harris, Brandon Scott; Schmalz, Dorothy
ABSTRACT: This conceptual article examines how existing institutionalized sexism constructed within fraternity party structure is used as a mechanism for categorizing women on college campuses. While these social gatherings provide an opportunity for interaction and new relationships, the environment is often constructed in a manner that reinforces traditional gender roles and increases the overall risk of sexual assaults. For some females, the attainment of status and social acceptance appears to be more important than the risk involved with attendance. The descriptive model presented focuses on the categories of relationships and the risk associated with assimilating into the fraternity party culture.